Assessment of occupational hazards, health effects, and personal protective equipment usage among motorcycle food delivery riders in Thailand: a cross-sectional survey - Siriaran Kwangsukstith; Vithawat Surawattanasakul; Chollada Mahakkanukrauh; Jinjuta Panumasvivat; Wachiranun Sirikul (Journal of Occupational Medicine and Toxicology)
Abstract Background Motorcycle Food Delivery Riders (MFDRs) play a vital role in the online food delivery industry, yet their prolonged time on the road exposes them to numerous occupational hazards, health risks, making them more vulnerable than both regular motorcyclists and the general population. The study aimed to investigate the working conditions, occupational hazards, health issues, use of personal protective equipment (PPE), and the association between occupational hazards and health effects among Thai MFDRs. Methods A cross-sectional study was conducted from November 2021 to mid-February 2022 in Chiang Mai, Thailand, using an anonymous self-reported survey. A total of 709 MFDRs participated in the survey. Data were collected on background information, job characteristics, occupational hazards, health issues, and the use of PPE over the previous six months. The data were analyzed using a multivariable logistic regression model. Results Most MFDRs are frequently exposed to physical hazards, including heat and sunlight (91.6%), as well as chemical hazards such as exhaust smoke (90.1%) and particulate matter (PM) (86.1%). Most MFDRs reported suffering from musculoskeletal disorders (62.1%) and eyes-related problems (45.1%). The most common problems were shoulder pain (39.2%), neck pain (38.1%), and burning eyes (33.3%). Multivariable logistic regression analysis indicates that biomechanical hazards are significantly associated with musculoskeletal disorders (MSDs) (p < 0.05), while psychological hazards significantly associated with headaches, insomnia, and feeling depressed (p < 0.05). Additionally, physical hazards such as sunlight and heat, noise, and whole-body vibrations, are also significantly associated with headaches, flu-like symptoms, and insomnia (p < 0.05). The most worn PPE by the participants were helmets (99.72%), long-leg pants (99.72%), masks (99.29%), and thermal jackets (98.17%). Conclusions The high prevalence of occupational hazards and health issues among MFDRs is worrisome. It is critical for platform companies and health sectors to introduce effective protective measures for workers, including establishing health surveillance, and supplying PPE.